Study on Compensation, Organizational Commitment, and Work Motivation for Employee Retention at a Local Hospital - Lila Maria Kaban; Umi Kulsum (Jurnal Multidisiplin Madani, 2023)
Human resource management is critical for hospitals but is frequently disturbed by employee retention issues. This research aims to determine the influence of compensation, organizational commitment, and work motivation on employee retention at Malahayati Medan. The research method applied is quantitative research by collecting data through questionnaires distributed from July to October 2022. The sampling method used is purposive sampling, with 78 employees as the sample. The data analysis method used is descriptive statistics, coefficient determination, multiple linear regression analysis, and hypothesis testing with t-test and F-test. The results of the t-test are compensation, organizational commitment, and work motivation partially influence employee retention. The results of the F test showed that all independent variables simultaneously influence employee retention and 61.1% of employee retention is influenced by compensation, organizational commitment, and work motivation. It is recommended for companies in similar industries pay attention to the results of this research